High-Tech-Gründungen in den neuen Bundesländern: Entwicklung und Standorte - Johannes Felder; Andreas Fier; Eric A. Nerlinger (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
New firm set ups, especially in High Tech industries, can give important impulses for the technological development and the catch up process in the Neuen Bundes1aender. The paper at hand gives an overview about the formation behaviour considering the preconditions of the former German Democratic Repub1ic (GDR) and the transformation process until reunification. Hereby it is necessary to make a distinction between genuine firm formations and firmations influenced by the privatisation process and the restructuring of former GDR-Kombinate, illustrated by the Kombinat Robotron. Less surprising, it becomes evident that there's a decline in the number of new firms from 1990 to 1993 in High Tech industries, heavi1iy differing between the individual Bundeslaender. These differences also occur in the 10cation behaviour of the firms. Regional clusters of formations in technology intensive industries can especially be found in the southern regions of East-Germany, whereas there are only less in the North and West of the Neuen Bundeslaender.
Keywords: 330; Unternehmensgründung; Hochtechnologiesektor; Räumliche Verteilung; Regionale Disparität; Agglomerationseffekt; Neue Bundesländer